Cada casa é um caso: uma etnografia da casa da mulher brasileira de São Luís-MA - SILVA, Maynara Costa de Oliveira (2022)
ABSTRACT For the care of victims of sexual violence, in São Luís/MA there is the Casa da Mulher Brasileira, one of the actions of the federal government program formerly named “Woman, live without violence”, today “Safe and protected woman”. of a public space that concentrates specialized services for the care of women in situations of violence, which has the service provided through a service network. This thesis analyzes, from an ethnographic perspective, the processes that forge the formation, the functioning and dynamics of the House. It was intended to understand how the State is made, what are the practices, actions and discourses of its administrators and how the representations of users are mobilized, emphasizing the categories crime, violence and victim. Thus, this ethnography is on the management of violence, the forms of state legibility, and the production of documents, laws and lives in one of the only Casas da Mulher Brasileira operating in Brazil until 2022.Thus, this ethnography is about the management of violence, memory of a public policy, as a form of state public readability, and the production of documents, laws and lives in one of the only Casas da Mulher Brasileira operating in Brazil until 2022.